Anatomical characteristics of the strawberry seedlings micropropagated using different sources of silicon - Braga, Francyane Tavares; Nunes, Cludinéia Ferreira; Favero, Ana Carolina; Pasqual, Moacir; Carvalho, Janice Guedes de; Castro, Evaristo Mauro de (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the effect of different silicon sources, used in micropropagation, on the anatomical characteristics of strawberry’s (Fragaria x ananassa) seedlings. Propagules of cv. Oso Grande were cultivated on a Murashige and Skoog (MS) medium containing 30 g L-1 of sucrose, 6 g L-1 of agar and 1 mg L-1 of 6-benzylamino purine. The treatments consisted of calcium, sodium, or potassium silicates added to the MS medium, at the dosage of 1 g L-1. The MS medium without added silicon was the check treatment. The experimental design was completely randomized with ten replications. The propagules were maintained during 45 days in a growth chamber, under controlled conditions. Developmental and anatomical characteristics of the in vitro propagules were evaluated. Fresh and dry weight of the propagules increased in the presence of sodium silicate. The supplementation of the culture medium with silicon increased the content of chlorophyll. The addition of sodium silicate in the MS medium resulted in increased thickness of leaf tissues and epicuticular wax deposition and in increased silicon deposit in the cells.